Character Education Based on Islamic Values in Shaping Students' Morals Based on the Curriculum of Love - Ulva badi' Rohmawati; Bendaoud Nadif (CV. Agrapana Media, 2026)
Students' moral decline is increasing due to weak internalization of Islamic values. This study aims to analyze the internalization of Islamic values in character education through the implementation of a love-based curriculum and its influence on the formation of students' morals. The study also focuses on the role of the love-based curriculum as a pedagogical approach in strengthening the effectiveness of character education. This research uses a qualitative approach with a case study design carried out at MI Fattahul Huda. Data collection techniques were conducted through observation, interviews, and documentation, and then analyzed using an interactive analysis model that includes data reduction, data presentation, and conclusion drawing. The results of the study indicate that the internalization of Islamic values occurs effectively through habituation, role modeling, communication, and meaningful learning experiences. Character education based on Islamic values has been proven to be able to shape students' morals, which include discipline, honesty, empathy, responsibility, and self-control